2003
DOI: 10.1074/jbc.m213006200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Statin Bound to a Class II Hydroxymethylglutaryl-CoA Reductase

Abstract: Hydroxymethylglutaryl-CoA (HMG-CoA) reductase is the primary target in the current clinical treatment of hypercholesterolemias with specific inhibitors of the "statin" family. Statins are excellent inhibitors of the class I (human) enzyme but relatively poor inhibitors of the class II enzymes of important bacterial pathogens. To investigate the molecular basis for this difference we determined the x-ray structure of the class II Pseudomonas mevalonii HMG-CoA reductase in complex with the statin drug lovastatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 28 publications
(35 reference statements)
1
48
0
Order By: Relevance
“…The ternary structures also revealed that Lys267 participates in catalysis and substrate binding, which was subsequently confirmed by mutagenesis and kinetic studies (4,5). The crystal structure of P. mevalonii HMG-CoA reductase has been solved by using a complex with the inhibitor lovastatin (24). Lovastatin binds in the central HMG pocket, accommodating itself in the same position as mevalonate and the HMG portion of HMG-CoA (Fig.…”
Section: P Mevaloniimentioning
confidence: 67%
“…The ternary structures also revealed that Lys267 participates in catalysis and substrate binding, which was subsequently confirmed by mutagenesis and kinetic studies (4,5). The crystal structure of P. mevalonii HMG-CoA reductase has been solved by using a complex with the inhibitor lovastatin (24). Lovastatin binds in the central HMG pocket, accommodating itself in the same position as mevalonate and the HMG portion of HMG-CoA (Fig.…”
Section: P Mevaloniimentioning
confidence: 67%
“…1,2 However, the drugs bind with inhibition constants in the micromolar range and therefore less tightly to the HMGRs of pathogenic bacteria. 18,19 This observation is explained in part by protein sequence alignments of the known HMGR enzymes. Two evolutionarily divergent classes of HMGRs that split roughly by eukaryotes (Class I) and prokaryotes (Class II) were discovered.…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with the residues implicated in catalysis and substrate binding. It also displaced the flap domain of the enzyme which contained the catalytic residue His-381 [13,40,41,52]. This binding with statin prevented HMG-CoA reductase from attaining the functional state.…”
Section: Fig (2b)mentioning
confidence: 99%
“…For the HMG-CoA reductase of P. mevalonii, the catalytic domain contains three conserved acidic residues, viz., Glu 52, Glu 83, and Asp 183 [11,12]. Tabernero et al [13] reported the crystal structure of a lovastatin bound to both class I (human) and class II (bacterial) HMG-CoA reductases. This work gives an impetus for the development of selective class II inhibitors for use as antibacterial agents against pathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%